Impact of February 6, 2024 Earthquakes on Community Resilience - Kaya, Aşır Yüksel (My University, 2025)
This study explores the interaction of people and place, the most important elements of geography, in the context of community resilience. Community resilience is the process of adaptation of a society to changing conditions by recovering from the effects of disasters as soon as possible. A resilient community is considered one of the most important components of disaster respons. In the context of increasing disaster risks, interest in increasing community resilience is growing in both academic and policy circles. This study seeks to understand how individuals affected by the February 6, 2023, earthquakes perceive resilience. These interviews were conducted as qualitative research. Typical case sampling was used in the study. Participants were selected from individuals who had experienced both earthquakes (January 24, Elazig and February 6, 2023, Kahramanmaraş) and equal gender distribution was sought. Interviews were conducted on July 15 and August 15, 2023, six months after the second earthquake. Interviews were conducted with 22 people, consisting of 11 female and 11 male earthquake survivors from Elazig, Kahramanmaraş, and Malatya, the three provinces affected by the earthquake. A descriptive analysis of the opinions obtained after the interviews was conducted. Similar answers were brought together, and conclusions on social resilience were evaluated in terms of social, environmental, economic, built, natura, and institutional environment dimensions.
Keywords: Resilience; Disaster; Urban Resilience; Comunity Resilience; Earthquake Resilience